Choctaw nation : a story of American Indian resurgence - Lambert, Valerie (University of Nebraska Press, 2007)
Choctaw Nation is a story of tribal nation building in the modern era. Valerie Lambert treats nation-building projects as nothing new to the Choctaws of southeastern Oklahoma, who have responded to a number of hard-hitting assaults on Choctaw sovereignty and nationhood by rebuilding their tribal nation. Drawing on field research, oral histories, and archival sources, Lambert explores the struggles and triumphs of a tribe building a new government and launching an ambitious program of economic development in the late twentieth century, achieving a partial restoration of the tribe's former glory as a significant political and economic presence in what is now the United States.
Keywords: Choctaw Indians -- History.; Choctaw Indians -- Social life and customs.; Choctaw Indians -- Government relations.; Southern States -- History.; Southern States -- Social life and customs.; Baseball players -- Taiwan -- History.; Joueurs de base-ball -- Taiwan -- Histoire.; États-Unis (Sud) -- Histoire.; HISTORY -- State & Local -- General.; Choctaw Indians; Choctaw Indians -- Government relations; Choctaw Indians -- Social life and customs; Manners and customs; Southern States; Choctaw (Indiens) -- Histoire.; Choctaw (Indiens) -- Relations avec l'État.; Choctaw (Indiens) -- Moeurs et coutumes.; Indiens d'Amérique -- États-Unis (sud); États-Unis (sud) -- Moeurs et coutumes.; History